Transcriptomic Profiling of the Adaptive and Innate Immune Responses of Atlantic Salmon to Renibacterium salmoninarum Infection - Eslamloo, Khalil; Caballero-Solares, Albert; Inkpen, Sabrina M.; Emam, Mohamed; Kumar, Surendra; Bouniot, Camila; Avendaño-Herrera, Ruben; Jakob, Eva; Rise, Matthew L. (Frontiers in Immunology, 2020)
Bacterial Kidney Disease (BKD), which is caused by a Gram-positive, intracellular bacterial pathogen (Renibacterium salmoninarum), affects salmonids including Atlantic salmon (Salmo salar). However, the transcriptome response of Atlantic salmon to BKD remained unknown before the current study. We used a 44K salmonid microarray platform to characterise the global gene expression response of Atlantic salmon to BKD. Fish ( 54 g) were injected with a dose of R. salmoninarum (H-2 strain, 2 × 108 CFU per fish) or sterile medium (control), and then head kidney samples were collected at 13 days post-infection/injection (dpi). Firstly, infection levels of individuals were determined through quantifying the R. salmoninarum level by RNA-based TaqMan qPCR assays. Thereafter, based on the qPCR results for infection level, fish (n = 5) that showed no (control), higher (H-BKD), or lower (L-BKD) infection level at 13 dpi were subjected to microarray analyses. We identified 6,766 and 7,729 differentially expressed probes in the H-BKD and L-BKD groups, respectively. There were 357 probes responsive to the infection level (H-BKD vs. L-BKD). Several adaptive and innate immune processes were dysregulated in R. salmoninarum-infected Atlantic salmon. Adaptive immune pathways associated with lymphocyte differentiation and activation (e.g., lymphocyte chemotaxis, T-cell activation, and immunoglobulin secretion), as well as antigen-presenting cell functions, were shown to be differentially regulated in response to BKD. The infection level-responsive transcripts were related to several mechanisms such as the JAK-STAT signalling pathway, B-cell differentiation and interleukin-1 responses. Sixty-five microarray-identified transcripts were subjected to qPCR validation, and they showed the same fold-change direction as microarray results. The qPCR-validated transcripts studied herein play putative roles in various immune processes including pathogen recognition (e.g., tlr5), antibacterial activity (e.g., hamp and camp), regulation of immune responses (e.g., tnfrsf11b and socs1), T-/B-cell differentiation (e.g., ccl4, irf1 and ccr5), T-cell functions (e.g., rnf144a, il13ra1b and tnfrsf6b), and antigen-presenting cell functions (e.g., fcgr1). The present study revealed diverse immune mechanisms dysregulated by R. salmoninarum in Atlantic salmon, and enhanced the current understanding of Atlantic salmon response to BKD. The identified biomarker genes can be used for future studies on improving the resistance of Atlantic salmon to BKD.